Pelatihan Dasar Membuat Aplikasi Android App Inventor Pada Sekolah Menengah Atas Saint Siak Sri Indrapura - Loneli Costaner; Bayu Febriadi; Guntoro (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Today's technology continues to grow rapidly which can be used to facilitate and support human activities, starting from the homework, business, marketing and office processes. So it takes knowledge to use technology-based facilities to improve human resources that are efficient for life independence. With the development of the world of digitalization technology is becoming evident before humans of this era, where in the past people for shopping and learning must come to the intended destination, but now people only stay at home or anywhere they can do their activities with just the touch of a finger. The ease of this facility is inseparable from the many Android-based applications to market products to be sold, both changing services, goods, and personnel. The condition of changing activities hard to soft activities is because the development of the digital era is very important for students to understand the development and training of Android-based applications in order to gain skills in designing Android-based applications open souce namely with an inventor app that can be used free of charge, its form visuals that make it easier for students to design and create android-based applications.